THE CORRELATION BETWEEN STUDENTS' MOTIVATION INDEXES AND THEIR ACHIEVEMENT SCORES IN ENGLISH CLASS(A CORRELATIONAL STUDY OF NINTH GRADERS OF SMPN 1 PACET, CIANJUR) - Yuni Kaspirawati, - (2008)
The main objectives of this research are to investigate the existence and the degree of the correlation between students' motivation indexes and students' achievement scores in English class. This Research involves the ninth graders of SMPN 1 Pacet, Cianjur as population and employs SPSS 16.0.1. in investigating the correlation. Since the normality of data distribution is violated, nonparametric statistical technique (Spearman correlation for ranked data) applied. The result shows that the value of is 0.309. It means there is a positive correlation between students' motivation indexes and their achievement scores in English class. The correlation coefficient is significant at 0.05level. By using the coefficient of determination (CD) formula, it is known that students' motivation indexes in learning English give 8.8% contribution to students' achievement scores in English class while the rest is influenced by other factors which are not investigated in this research. The result of this research only works at the samples of this research. If the similar research is conducted on different samples, the findings might be different.